Approaches to the Computer Vision System Proposal on Purposes of Objects Recognition within the Human-Robot Shared Workspace Collaboration - Rengevic, Alexander; Kumicakova, Darina; Kuric, Ivan; Tlach, Vladimír; Pawel Drozdziel (Communications - Scientific letters of the University of Zilina, 2017)
The article deals with the present topic of solution of the tasks of a safe cooperation between human and robot within industrial applications. The attention is aimed at the utilization of state-in-art devices of computer vision and related methods of object recognition within the monitored zone of the laboratory of automated assembly. The article presents some steps of the computer vision system design with focus on the suitable sensors selection and experimental verification of their parameters for demands of monitoring the specified safety zones. The designed computer vision system is one of the elements of the complex safety system that is in the process of designing in the laboratory workplace conditions.